(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Buot IE Jr, Buhay AFV. 2022. Review: Types of socioecological production landscapes of the Philippines based on dominant biodiversity: status, problems and future directions. Biodiversitas 23: 3755-3770. The dominance of human activities in socioecological production landscapes (SEPLs) known as biocultural landscapes in some literature, results in the overutilization of natural resources and loss of critically important biodiversity, either cultivated or wild. The anthropocentric perspective prevailing at this time of the Anthropocene Epoch, disrupts the traditional harmonious human-nature relationship in biocultural landscapes, particularly, the socioecological production landscapes (SEPLs) known as satoyama landscapes in Japan. This adversely affects biodiversity and hence, ecosystem services in surrounding communities in the Philippines and beyond. In this paper, SEPLs, biocultural landscape and satoyama are used interchangeably to refer to landscapes where human culture has greatly influenced the resulting biodiversity of a landscape. This study provides an overview of the SEPLs in the Philippine context. It reviews and furthers the inquiry in a previous study which identified examples of satoyama landscapes or SEPLs in the Philippines based on the main crop or dominant biodiversity. The objectives of the current paper are to present an updated list of SEPLs in the Philippines based on the main crop or dominant biodiversity; determine its status and problems; analyze its role in sustainable development and map future directions to sustain a harmonious human-nature relationship that would result to an abundance of biodiversity and overflowing ecosystem services. The local and international scientific literature on the status and problems of the identified SEPLs in the Philippines were reviewed. Results indicated that in addition to the three types identified by Buot and Osumi in 2004, nine more were included in this paper. The 12 SEPLs types identified were classified according to their main crop, namely: rice in muddy walled or stone-walled terraces; rice mixed with other crops; corn; vegetables, sweet potato, gabi/taro; cassava; coconut; coffee; cacao; tobacco; and rice-fish. These SEPLs contribute to various Sustainable Development Goals (SDGs), either directly or indirectly. Incidentally, there are prevailing problems observed such as exploitation of natural resources due to the increasing population of migrants in the upland as a result of poverty. Simultaneously, the indigenous sustainable practices were weakened with the aging population while the youth showed a lack of interest in farming, leading to biodiversity loss and cultural erosion. Strategic actions including strengthening institutional partnerships, empowering indigenous communities, sustainable management of natural resources, and ensuring good governance and equitable sharing of resources are discussed. These steps will ensure biodiversity conservation and harmonious living in Philippine SEPLs.